“Estudio del equilibrio de adsorción de la dureza del agua sobre rocas volcánicas.” - Gallo Tibanquiza, Lesly Estefanía (2020)
Hard waters show problems in health, industries and agriculture, that is why the this research aims to assess the balance of adsorption of water hardness on rock beds of the volcanoes; El Altar, Chimborazo, Cotopaxi, Reventador and Tungurahua. At the beginning, the Δ pH of the volcanic material was analyzed, and 0,5 and 1,5 cm size beds were prepared, in order to assess the speed and the mechanism with which the hardness is adsorbs on the surface of the different rocks. To do this tests, a standard solution of initial concentration of 635 ppm CaCO3 was prepared and adsorption on natural beds and activated with NaOH and HCl was studied. The results indicate that the 5 volcanic beds adsorb the hardness of the water, each one in greater or lesser quantity, depending on the physical and chemical characteristics of each material, the beds activated with NaOH were more efficient to the natural beds. In addition, each of them implies that it has a specific isotherm, which is maintained if it is activated with NaOH or if a natural bed is used, the Temkin model predominates for the volcanic beds of Cotopaxi and Tungurahua; the Langmuir model for Reventador and Chimborazo, and the Dubbinin-Radushkevich model for El Altar, only changes were observed in the isotherm type when activated with HCl, determining that, for the beds of the Chimborazo volcano, Cotopaxi and Tungurahua they were adjusted to the Dubbinin-Radushkevich model, while for El Altar and Reventador they were adjusted to Temkin's isotherm. All the adsorption processes studied follow a pseudo second order kinetics.